Assessment of the acaricidal efficacy of Rosmarinus officinalis essential oil against dogs’ ticks, Rhipicephalus sanguineus (Acari: Ixodidae), and its chemical composition. - Abdelali, Salma; Souttou, Karim; Kacimi-Elhassani, Mohamed; Aissaoui, Lynda (Revista de Ciências Agroveterinárias, 2024)
Ticks play the main role, in veterinary terms, in transmitting important pathogens. Rhipicephalus sanguineus is a widespread tick known for its ability to thrive in indoor environments and could be the main reservoir host for many TBDs. In this study, the acaricidal and larvicidal potential of Rosmarinus officinalis essential oil was evaluated against R. sanguineus. The aerial part of this plant was extracted by hydrodistillation and then analyzed by gas chromatography coupled with mass spectrometry (GC/MS). The yield obtained from this oil was 0.38%, its major chemical compounds were found to be Camphor (43.52%), Eucalyptol (13.66%), and Camphene (13.2%). The adult immersion test (AIT) using four concentrations (1µl/ml,2µl/ml,10µl/ml, 30µl/ml) revealed that this oil presented oviposition reduction percentages of 5.75%, 20.68%, 33.27%, and 46.84%, hatching reductions percentages of 5%, 15%, 35%, and 60%, and efficacy extract percentages of 10.46%, 32.58%, 56.63%, and 78.74% Further, the larval immersion test (LIT) using five concentrations (0.5µl/ml,1µl/ml, 2µl/ml, 3µl/ml, and 5µl/ml) revealed considerable larvicidal activities with LC50 and LC90 values of 2.286 µl/ml and 5.380 µl/ml, respectively. These results are encouraging and open interesting and promising horizons for its application as a bio-acaricide.